PEMBERIAN PUPUK UREA PADA TANAMAN KANGKUNG DARAT (IPOMOEA REPTANS POIR) DENGAN JARAK TANAM YANG BERBEDA - ANAK AGUNG GEDE PUTRA; I NENGAH KARNATA; KETUT TURAINI INDRA WINTEN (GANEC SWARA, 2022)
Ground kale (Ipomoea Reptans Poir) is one of the agricultural commodities that can be traded at a relatively expensive price. Spinach plants that are relatively resistant to drought andhave a broad adaptability to varius growing environmental conditions, estimated at 2-3 times per year so that the cash flow of the vegetable business will be faster. An incease in demand with demands for better quality vegetable commodities, as well as more guaranteed survival. The estimated annual vegetable demand rate of 8% is good for consumption in the contry, import substitution and in increasing export opportunities. Regulating plant density to a certain extent, the plants can utilize the growing environment efficiently, and the inorganic fertilizer becauseit has a Nitrogen (N) content of 46%. Where nitrogen is a major component of varius important substances in plant. About 40% of the protoplasm content consists of nitrogen compounds used by plants to form amino acid  compounds that are comperted into proteins, chlorophyll,nucleic acids and enzymes.This study was conducted to determine the effect of spacing and dose of N as well as its intrinsic growth and yield of ground water spinach plants,and was carried out in the Subak Tungkub Mengwi region, Mengwi Village, Mengwi District, Badung Regency, with a height of ± 400 m above sea level. The study began from December 8, 2020 until Januari 5, 2021 for 28 days from planting seeds to harvest. This study uses a randomized blok design (RBD) consisting of two factor. The first factor is plant spacing (J) and the second factor is the dose of Urea (U), each treatment is repeated three times.The economical oven dry weight of plants at the distance of plant spacing with the average oven dry weight of economic clump-1 was 5,25 g, with the highest value indicated in the treatment (J1) was 5,34 g while the highest value of Urea dose was shown at dose (U2) of 7,74 g increasing 23,84% compared to the oven dry weight of the lowest clump-1 economy of 6,25 g